Decrease in the Rate of Non-curricular Reading among Students: Causes, Consequences and Solutions - Mazhar Babaee; Asra Asra Zare-Ramashti; Kowsar Azizan (تحقیقات اطلاع‌رسانی و کتابخانه‌های عمومی)
Objective: The purpose of the research was to identify the effective factors in decreasing the rate of reading among the students of Farhangian University of Kurdistan province as well as expressing the consequences and providing solutions. Method: The paradigm of interpretivism with a qualitative approach and content analysis strategy of descriptive type of written text and descriptive-analytical text format were used in this study. The participants were student-teachers of Farhangian University of Kurdistan province in the academic year of 2021-2022 with using conventional sampling method. The data collection tool was a semi-structured interview made by the researchers that was sent to 60 people in a virtual environment and in the space of the learning management system (LMS). Data were analyzed by open and axial coding methods. Results: The findings were analyzed in three sections: causes, consequences and solutions. The causes in 9 categories and 111 concepts included cultural and social, economic, individual and personal, virtual space and media, books, librarians and libraries, government sector, friends and family, school and university, and authors, publishers and translators. In the consequences section, 3 categories including mental and cognitive poverty, moral consequence and cultural and social poverty were examined in 132 concepts, and in the solutions section, 7 categories including cultural and social solutions, economic solutions, individual perspective solutions, librarian solutions, libraries, book publishers and translators, solutions of the government sector, solutions of family and friends, and solutions of the university were identified in 127 concepts. Conclusions: The current research has been able to identify the causes and consequences of the decrease in reading rates among students and then identify solutions to reduce them. Public libraries can play an effective role in the application of these solutions while interacting with students on the one hand and the government on the other hand.